2016
DOI: 10.1039/c6cy00990e
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and mechanisms of alcohol dehydration pathways on alumina materials

Abstract: The steady state rates of ethene and diethyl ether formation in parallel ethanol dehydration reactions at 573 and 623 K are mechanistically and kinetically described by the same rate expression on different alumina materials (α-, γ-, and η-Al 2 O 3 ), implying that alumina materials have similar surface sites under reaction environments. In situ chemical titration using pyridine as a titrant elucidates similar site densities (∼0.12 sites nm −2 and ∼0.07 sites nm −2 for ethene formation and ∼0.14 sites nm −2 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 62 publications
0
33
0
Order By: Relevance
“…54 In gas-phase alcohol dehydration reactions, H 2 O inhibits the rates of forming both alkenes and ethers in unimolecular and bimolecular pathways, respectively. 55 H 2 O inhibition quantied by negative reaction orders is oen described by reaction mechanisms that include inhibitory alcohol-water dimer species, as observed in alcohol dehydration catalyzed by Brønsted acidic Keggin-type polyoxometalate clusters 56 and Lewis acidic g-Al 2 O 3 57,58 and Sn-Beta zeolites. 59,60 Others have suggested that co-adsorbed H 2 O inhibits alcohol dehydration by stabilizing adsorbed alcohols preferentially over transition states, in the case of 1-propanol dehydration on H-Al-MFI zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…54 In gas-phase alcohol dehydration reactions, H 2 O inhibits the rates of forming both alkenes and ethers in unimolecular and bimolecular pathways, respectively. 55 H 2 O inhibition quantied by negative reaction orders is oen described by reaction mechanisms that include inhibitory alcohol-water dimer species, as observed in alcohol dehydration catalyzed by Brønsted acidic Keggin-type polyoxometalate clusters 56 and Lewis acidic g-Al 2 O 3 57,58 and Sn-Beta zeolites. 59,60 Others have suggested that co-adsorbed H 2 O inhibits alcohol dehydration by stabilizing adsorbed alcohols preferentially over transition states, in the case of 1-propanol dehydration on H-Al-MFI zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…This tendency could be explained by numbers of acid sites, as indicated by the NH 3 -TPD experiment. Bhan et al also reported that ethanol conversion increased with the number of acid sites [41]. Figure 6b shows ethylene selectivity as a function of reaction temperature for the ZN-supported WO x samples.…”
Section: Ethanol Conversion Studiesmentioning
confidence: 75%
“…Of those products, ethylene and acetaldehyde are formed by an intramolecular reaction, whereas DEE is formed by an intermolecular reaction [40]. Bhan et al showed, using in situ pyridine titration experiments, that both reactions are catalyzed by acid sites [41]. Beta(β) C-H bond cleavage is the rate-limiting step in the synthesis of ethylene and, after this bond has been broken, ethylene is formed with the concomitant release of water [40].…”
Section: Ethanol Conversion Studiesmentioning
confidence: 99%
“…Alumina is basically a good choice due to its high selectivity, low cost, and high resistance and lifetime, and the mechanism in alcohol dehydration with respect to the structure and acidity has been largely studied [27,28].…”
Section: The Use Of Solid Acids In Dme Synthesismentioning
confidence: 99%